LUMBAR DISC HERNIATION IN PATIENTS WITH CHRONIC BACKACHE - Ali, Asghar; Khan, Shahbaz Ali; Aurangzeb, Ahsan; Ahmed, Ehtisham; Ali, Gohar; Muhammad, Gul; Mehmood, Shakir (Journal of Ayub Medical College Abbottabad, 2013)
Background: Low back pain with or without lower extremity pain is the most common problem among chronic pain disorders with significant economic, social, and health impact. This study was conducted to determine the frequency of lumbar disc herniation and its different levels, among patients with chronic backache. Methods: This cross sectional study was conducted in the department of Neurosurgery, Ayub Medical College Abbottabad from January 2011 to January 2013. All the patients presenting with chronic low backache of either gender above the age 14 years were included in the study. Magnetic resonance imaging (MRI) was done in all the patients included in the study to look for lumbar disc herniation. Results: A total of 477 patients with chronic low backache were included in the study out of which 274 (57.4%) were males. Age of the patients ranged from 19 to 75 (39.92±12.31) years. Out of 477 patients 38 (7.9%) had significant radiological evidence of disc prolapse at lumbar vertebral levels, with 26 (9.5%) males and 12 (5.9%) females. Among these 38 patients with inter-vertebral disc, 20 (52.6%) of patients had disc herniation at L5-S1, 15 (39.5%) at L4-L5, 2 (5.26%) cases at L3-L4 level and only one case (2.6%) had the involvement of L2-L3 level. No cases of L1-L2 disc prolapse were found. Conclusion: Patients with chronic backache can have inter-vertebral lumbar disc prolapsed disease. Middle age group are more affected by lumbar disc disease especially at the lower lumbar regions. Keywords: Backache, inter-vertebral disc, lumbar disc, magnetic resonance imaging